5-Ethyl-2-Hydroxy Acetophenone Oxime as an Analytical Reagent— Studies on Cu(II) Chelate - T.M. Desai, Mrs. (Asian Journal of Chemistry, 2010)
2-Hydroxy-5-ethyl acetophenone oxime was synthesized and used as an analytical regent for copper. The structure of the buff coloured Cu(II) complex has been assigned on the basis of Job's method, mole-ratio method and IR-structural data.